Phytonematode population dynamics in common bean cultivation under crop rotation and no-tillage conditions - Bernabé Santos, Letícia; D’Amico-Damião, Victor; Fernandes de Souza, Vinícius; Ferreira Junior, Rivanildo; Borges Lemos, Leandro; Martins Soares, Pedro Luiz (Revista Ceres, 2022)
Strategies for conserving natural resources and reducing agricultural inputs are the great challenge for agriculture, such as sustainable alternatives to control agricultural pests of high economic impact, e.g. plant-parasitic nematodes. This work aimed to evaluate phytonematode’s population dynamics in common bean cultivation grown under crop rotations and no-tillage system. The maize was seeded under pearl millet straw and intercropped with three different crops systems: i) exclusive maize system, ii) maize intercropped with brachiaria and, iii) maize intercropped with crotalaria. The experimental design was a randomized complete block with three treatments (crops systems) and 4 blocks (5 subsamples each block). The common bean was seeded on the straw of exclusive or intercropped maize. The phytonematode population was evaluated in the soil and in the roots in seven moments: (i) fallow; (ii) pearl millet flowering; (iii) pearl millet maturity; (iv) maize flowering; (v) maize maturity; (vi) common bean flowering; and (vii) common bean maturity. The greatest control of the phytonematodes species described in the area was in the maize intercropped with crotalaria treatment, as the phytonematodes population decreased 2.49-fold in this treatment when compared to exclusive maize, resulting in an increase of 11.27% in common bean yield. Therefore, maize intercropped with crotalaria is a viable alternative to reduce phytonematodes infestation in common bean crop.